IMPLEMENTASI SISTEM PENGAMANAN ASET DI MASJID MENGGUNAKAN CCTV TERINTEGRASI DENGAN PENERANGAN OTOMATIS - Kiswanta, Kiswanta; Setyo P, Yoyok Dwi; Agus N., Woro; Abdul R, Ojak; Suminto, Suminto (Universiitas Pamulang, 2021)
ABSTRACT Nowadays, the role of mosques or mosques in social activities is also getting stronger. The existence of an organization that organizes or manages mosque household, such as the DKM (Mosque Prosperity Council/Musholla), IPM (Muslim Mosque/Musholla Youth Association), IRM (Muslim Mosque/Musholla Youth Association) and so on, makes many mosques or prayer rooms always busy with activities. social community. Especially with the moment of Ramadan, of course there are more and more activities being held. Departing from the crowds of people who worship every day, especially in the month of Ramadan, which of course also involves a lot of congregation, the vigilance of the congregation who brings motorized vehicles and other items needs to always be reminded by the manager of the mosque or mosque. So far, there are 2 ways that are still quite effective in suppressing these dishonorable acts, namely providing security for mosques or prayer rooms and installing CCTV camera networks. The Ahsanu Amala Mosque has been built 14 years ago, even though it has undergone several renovations, but until now it has never installed security devices or used the services of security personnel, even though there has been a very frequent criminal act of theft of charity boxes in mosques and motorized vehicles. pilgrims in the vehicle parking area. The large number of worshipers who perform worship is not balanced with a good security supervision system as well as frequent power outages so that the situation becomes pitch black and becomes increasingly prone. Thus, we have installed CCTV security devices in 4 (four) strategic location points of the mosque, equipped with a monitor and video recorder to record video and automatic lighting so that all the people or congregation around can be more comfortable and devoted to worship. Keywords: CCTV, Security, Automatic Emergency Lights, and Community Service ABSTRAK Dewasa ini, peran masjid atau masjid dalam kegiatan sosial juga semakin kental. Adanya organisasi penyelenggara atau pengelola rumah tangga masjid, seperti DKM (Dewan Kemakmuran Masjid/Musholla ), IPM (Ikatan Pemuda Masjid/Musholla), IRM (Ikatan Remaja Masjid/Musholla) dan lain sebagainya, menjadikan banyak masjid atau musholla yang selalu ramai dengan kegiatan sosial kemasyarakatan. Apalagi dengan momen bulan Ramadhan, tentu saja semakin banyak kegiatan yang diselenggarakan. Berangkat dari ramainya orang yang beribadah setiap hari, terutama di bulan Ramadhan yang tentunya juga melibatkan banyak jamaah, kewaspadaan dari para jamaah yang membawa kendaraan bermotor dan barang-barang lainnya perlu selalu ditingatkan oleh pengelola masjid atau musholla. Sejauh ini, terdapat 2 cara yang masih cukup efektif untuk meredam aksi-aksi tidak terpuji tersebut, yakni menyediakan tenaga keamanan masjid atau musholla dan memasang jaringan kamera CCTV. Masjid Ahsanu Amala sudah dibangun sejak 14 tahun yang lalu, walau sudah mengalami beberapa kali renovasi bangunan namun hingga saat ini belum pernah memasang perangkat keamanan ataupun menggunakan jasa tenaga keamanan, padahal sudah sangat sering terjadi tindak pidana pencurian kotak amal di dalam masjid maupun kendaraan bermotor milik jamaah di area parkir kendaraan. Banyaknya jamaah yang melakukan ibadah tidak diimbangi dengan sistem pengawasan keamanan yang baik juga sering adanya pemadaman listrik sehingga keadaan menjadi gelap gulita menjadi semakin rawan. Dengan demikian kami telah melakukan pemasangan perangkat kemanan CCTV di 4 (empat) titik lokasi strategis Masjid tersebut dilengkapi monitor dan video recorder untuk merekam video serta lampu penerangan otomatis agar semua masyarakat atau jamaah sekitar bisa lebih nyaman dan khusuk beribadahnya Kata Kunci: CCTV, Keamanan, Lampu Darurat Otomatis, dan Pengabdian Masyarakat